PARSIFAL - Pershagen, Göran (Karolinska Institutet, 2012)
The international project PARSIFAL (Prevention of Allergy - Risk factors for Sensitization In children related to Farming and Anthroposophic life Style) Is directed from the Institute of environmental medicine at the Karolinska institute, and consists of children from the Netherlands, Switzerland, Sweden, Germany and Austria. Participants were primary selected from schools in rural areas, attending anthroposophic schools or living on farms. Children not living on farms and attending other schools were selected as references. The study design has been described in detail (Alfvén et al 2006). A total of 14,893 children, age 5-13 years participated. The parents answered a questionnaire providing information regarding homeenvironment, food, medical history and socioeconomi. Exposure and lifestyle factors related to the agricultural environment and anthroposophi was focused on.

Purpose:

The purpose of PARSIFAL is to study protective factors for allergy development in children raised at farms or in anthroposophic environments.

Det internationella projektet PARSIFAL (Prevention of Allergy - Risk factors for Sensitization In children related to Farming and Anthroposophic life Style) leds ifrån enheten för Miljömedicinsk epidemiologi vid IMM och baseras på barn från Nederländerna, Schweiz, Sverige, Tyskland och Österrike. Dessa valdes främst från skolor på landsbygden att identifiera barn som bor på en bondgård samt kontroller, liksom från Waldorfskolor (med antroposofiska barn) samt kontroller. Studieuppläggningen har beskrivits i detalj (Alfvén m fl 2006). Totalt ingår 14 893 barn i åldern 5-13 år, vars föräldrar i en enkät lämnat information om hemmiljö, kost, sjukdomshistoria och socioekonomiska förhållanden (svarsfrekvens: 69%). Exponeringar och livsstilsfaktorer relaterade till jordbruksmiljö och antroposofi fokuserades särskilt. Blodprov erhölls från 4050 barn, vilket utgör 67 procent av de som erbjöds medverka i denna del av studien. Fenotypning baserades på internationellt validerade enkätfrågor och allergen-specifika IgE-analyser. Genotypning har genomförts för 3113 barn efter samtycke från föräldrarna.

Syfte:

Syftet med PARSIFAL är att studera skyddsfaktorer för allergiutveckling hos barn uppväxta på bondgård eller i antroposofisk miljö.
PARSIFAL
Keywords: Blood Specimen Collection; Blodprovstagning; Life Style; Livsstil; Socioeconomic Factors; Socioekonomiska faktorer; Risk Factors; Riskfaktorer; Diet; Kost; Allergens; Allergener; Medical History Taking; Anamnes; Anthroposophy; Antroposofi; Child; Barn; Epidemiology; Epidemiologi; Phenotype; Fenotyp; Genotype; Genotyp; Agriculture; Lantbruk; Environmental Exposure; Miljöexponering; Hypersensitivity; Överkänslighet; HEALTH; HÄLSA; Respiratory Medicine and Allergy; Lungmedicin och allergi